(untitled) (TAMADDUN NURI JURNALI, 2025)
In today’s conditions of globalization, in most countries of the world, such ideas as democracy, freedom, and building a society of deficit are becoming important and relevant. By paying attention to world history, we are now convinced that every nation unites and develops based on its national idea, going through difficult trials. In the current conditions of globalization, ideological tension becomes, in some ways, more humiliating and dangerous than ideological dumping. This is because governing society requires a certain ideological program or theory. And this task must be carried out by ideology. Since without ideology, there is no political administration, and it will lack political institutions. Therefore, it serves as a manager, organizing public life, and programs, doctrines guiding towards a specific goal. Ideology is directly linked to politics. A change in policy cannot help but affect ideology.